Conformal subfoliations of prescribed geodesic curvature - Baird, Paul; Burel, Jean-Marie (MATHEMATICA SCANDINAVICA, 2003)
Given a 2-dimensional conformal foliation F of a Riemannian manifold M, the problem of finding a 1-dimensional subfoliation G, conformal in M, whose leaves have prescribed geodesic curvature in the leaves of F is equivalent to a Pfaff differential system on a circle bundle over M. We study such pairs of foliations on a 3- and 4-manifold.